1985
DOI: 10.1021/ja00299a023
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of quantum molecular models. 75. Comparative tests of theoretical procedures for studying chemical reactions

Abstract: Acknowledgment. This work was supported by PHS Grant CA 28824. NMR spectra were obtained through the auspices of the Northeast Regional NSF/NMR Facility at Yale University, which was supported by NSF Chemistry Division Grant CHE 7916210.Supplementary Material Available: An ortep drawing of compound 32 as well as the procedures related to the solution of the crystal structure, thermal parameters (Table I), bond distances (Table II), and bond angles (Table III). Experimental protocols for the preparative work, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(117 citation statements)
references
References 0 publications
1
114
1
1
Order By: Relevance
“…3 ab initio and semiempirical. Of these, ab Any semiempirical method is composed of initio, having no need for empirically detera theoretical framework and a set of paramemined parameters, is the more theoretically ters.…”
Section: Introductionmentioning
confidence: 99%
“…3 ab initio and semiempirical. Of these, ab Any semiempirical method is composed of initio, having no need for empirically detera theoretical framework and a set of paramemined parameters, is the more theoretically ters.…”
Section: Introductionmentioning
confidence: 99%
“…Following suggestions from Dewar [9] and Delley [10], as further explored by Delley [11], and Grimme [12], Csonka, Ruzsinszky, Tao and Perdew [2] found that the MAE's of the atomization energies for functionals on all rungs of the ladder…”
Section: Atomization Energy Puzzlementioning
confidence: 92%
“…The calculation process of the molecular descriptors is described as below: All molecules were drawn into Hyperchem, and pre-optimized using MM+ molecular mechanics force field. A more precise optimization was done with semiempirical AM1 [10] method in MOPAC [11]. The molecular structures were optimized using the Polak-Ribiere algorithm until the root mean square gradient was 0.001.…”
Section: Methodsmentioning
confidence: 99%